Some Aspects of Structural Modeling of Damage Accumulation and Fracture Processes in Metal Structures at Low Temperature. (27th July 2016) - Lepov, Valeriy; Grigoriev, Albert; Achikasova, Valentina; Lepova, Kyunna
Abstract : The problem of brittle fracture of structures at low temperature conditions connected to damage accumulation and ductile-brittle transition in metals. The data for locomotive tire contact impact fatigue and spalling are presented. The results of experimental testing showed the impact toughness drop at low temperature. The internal friction method was applied to revealing of the mechanism of dislocation microstructure changes during the low temperature ductile-brittle transition. It has been shown for the first time that the transition is not connected to interatomic interactions but stipulated by thermofluctuation on nucleus such as microcracks and by their further growth and coalescence. From now on, the proposed mechanism would be used for theoretical and numerical modeling of damage accumulation and fracture in materials.